Technical note: a compact data logger for ambulatory skin temperature measurement - Bolton, M P; McGuinness, K; Cooley, J; Hayes, L; Howell, A (Journal of medical engineering & technology, 2001)
A miniature, body-worn data logger has been developed for multi-channel recording of small changes in skin surface temperature. The unit has been designed for small size, long battery life and high accuracy together with full programmability and an infra-red (contactless) transfer of parameters and data. Temperature is measured using thermistors with a resolution of 0.005 degrees C and an absolute accuracy of better than 0.05 degrees C. A comprehensive software package running on a laptop PC is used for initial setting of the logger parameters and downloading and displaying the temperature data. The present system records eight channels of temperature at intervals from 30 seconds to 99 minutes. It contains 64 K bytes of non-volatile memory allowing 3274 sets of readings including subject identification, battey status, date and time. The logger size is 55 mm x 31 mm x 9.5 mm and weighs 20 g.